Which One is More Literary - A Speech or a Visitor's Guide? - Andrew, Yau-hau Tse (2011)
The use of texts as a source of data to test ideas or hypotheses is not widespread, but neither is it rare. The objective of this paper is to analyse two different types of texts and to determine which one is more literary than the other. CarterÃ¢ÂÂs (2004) model of literariness is used for the analysis. The findings reveal that the speech (text a) is dependent on itself and contains examples of stylistic and lexical features, words of contrast at text and sound level, parallelism, evocative descriptive language and cross-sentential repetition. The Greece tourist guide (text b) is medium independent and carries examples of archaic and syntactic features, emotive action verbs, evocative descriptive language, polysemy and displaced interaction. To conclude, it is quite difficult to measure which text is more literary unless the two texts are of identical genre.